Psychiatric Morbidity among Children and Adolescents Attending Psychiatric Clinic of a Tertiary Hospital - Sharma, Bhaskkar; Shrestha, Rajesh (Journal of College of Medical Sciences-Nepal, 2021)
Introduction: A variety of psychiatric manifestations can be seen in children and adolescents below the age of 19 years. This study aims to examine the socio-demographic, morbidity profiles, and clinical correlates of child and adolescent patients attending the psychiatry out-patient clinic of Lumbini Medical College and Teaching Hospital (LMCTH). Methods: It was an observational, cross-section study involving case record analysis of all children and adolescent patients attending the psychiatry out-patient clinic between December 1, 2018 to November 30, 2019 in LMCTH, Nepal. Socio-demographic and clinical data were entered into computer software and analysed. Results: One hundred and forty cases fulfilling inclusion criteria were included in the study. There were 96 (68.6%) females and 44 (31.4%) males. Majority of the patients were from 16-19 years age-group. Cases from urban areas predominated the picture. Most common psychiatric diagnosis was conversion disorder (29, 20.7%) followed by depressive disorder (25 or 17.9%) and anxiety disorder (14, 10%). Majority of females had conversion disorder (25 or 26%) followed by seizure disorder (23, 24%) and depressive disorder (15, 15.6%) whereas majority of males had equal count of depressive disorder and seizure disorder (10, 22.7%) followed by anxiety disorder (7, 15.9%). Conclusions: Psychiatric illness was most common in children and adolescents in the age group 16-19 years, followed by 11-15 years age-group. They were more common in female sex, and slightly higher in those from urban background. Common psychiatric diagnoses were conversion disorder followed by depressive disorder and anxiety disorder.